Super resolution using sparse sampling at portable ultra-low field MR - Donnay, Corinne; Okar, Serhat V.; Tsagkas, Charidimos; Gaitán, María I.; Poorman, Megan; Reich, Daniel S.; Nair, Govind (Frontiers in Neurology, 2024)
Ultra-low field (ULF) magnetic resonance imaging (MRI) holds the potential to make MRI more accessible, given its cost-effectiveness, reduced power requirements, and portability. However, signal-to-noise ratio (SNR) drops with field strength, necessitating imaging with lower resolution and longer scan times. This study introduces a novel Fourier-based Super Resolution (FouSR) approach, designed to enhance the resolution of ULF MRI images with minimal increase in total scan time.FouSR combines spatial frequencies from two orthogonal ULF images of anisotropic resolution to create an isotropic T2-weighted fluid-attenuated inversion recovery (FLAIR) image. We hypothesized that FouSR could effectively recover information from under-sampled slice directions, thereby improving the delineation of multiple sclerosis (MS) lesions and other significant anatomical features. Importantly, the FouSR algorithm can be implemented on the scanner with changes to the kspace trajectory.Paired ULF (Hyperfine SWOOP, 0.064 tesla) and high field (Siemens, Skyra, 3 tesla) FLAIR scans were collected on the same day from a phantom and a cohort of 10 participants with MS or suspected MS (6 female; mean±SD age: 44.1±4.1). ULF scans were acquired along both coronal and axial planes, featuring an in-plane resolution of 1.7mm x 1.7mm with a slice thickness of 5mm. FouSR was evaluated against registered ULF coronal and axial scans, their average (ULF Average) and a gold standard SR (ANTs SR).FouSR exhibited higher SNR (47.96±12.6) compared to ULF Coronal (36.7±12.2) and higher lesion conspicuity (0.12±0.06) compared to ULF Axial (0.13±0.07) but did not exhibit any significant differences contrast-to-noise-ratio (CNR) compared to other methods in patient scans. However, FouSR demonstrated superior image sharpness (0.025±0.0040) compared to all other techniques (ULF Coronal 0.021±0.0037, q=5.9, p-adj=0.011; ULF Axial 0.018±0.0026, q=11.1, p-adj=0.0001; ULF Average 0.019±0.0034, q=24.2, p-adj.<0.0001) and higher lesion sharpness (-0.97±0.31) when compared to the ULF Average (-1.02±0.37, t(543)=-10.174, p=<0.0001). Average blinded qualitative assessment by three experienced MS neurologists showed no significant difference in WML and Sulci or Gyri visualization between FouSR and other methods. FouSR can, in principle, be implemented on the scanner to produce clinically useful FLAIR images at higher resolution on the fly, providing a valuable tool for visualizing lesions and other anatomical structures in MS.